Survival Predictors of People Living with HIV/ AIDS in Wamena, Papua - Kogoya, Tena; Demartoto, Argyo; Murti, Bhisma (Indonesian Journal of Medicine, 2017)
Background: Quality of life (QoL) is an important component in the evaluation of the well-being of people living with HIV and AIDS (PLWHA), especially with the appreciable rise in the longevity of PLWHA. The analysis of the quality of life is essential for the healthcare policies and services directed toward PLWHA, since this indicator values the perception of people about their own life and health. However, little is known about the determinant of QoL in PLWHA in Papua. The aim of this study was to analyze survival predictors of people living with HIV/ AIDS in Wamena, Papua, Indonesia.Subjects and Method: This was a retrospective cohort study conducted in Wamena Hospital, Papua, from December 2017 to February 2018. A cohort of 304 PLWHA was selected for this study from the medical record at Wamena Hospital. The dependent variable was survival. The independent variables were adherence to ART, nutritional status, age, and coinfection. The data were collected from medical record and questionnaire. The data were analyzed by Cox regression model.Results: The risk of dying of PLWHA if adherent to take the ART was lower than not adherent to take the ART (HR=0.45; 95% CI= 0.06 to 0.33; p= 0.002).The risk of dying of PLWHA with poor nutritional status was higher than good nutritional status (HR= 12.78; 95% CI= 6.81 to 23.98; p< 0.001). The risk of dying of PLWHA aged ?35 years was slightly higher than <35 years (HR= 1.47; 95% CI= 1.00 to 2.17; p= 0.050). The risk of dying of PLWHA with coinfected was higher than without coinfected (HR= 1.59; 95% CI= 1.15 to 2.23; p= 0.006).Conclusion: The risk of dying of PLWHA decreases if adherent to take the ART, but increases with poor nutritional status, age ?35 years, and coinfection.Keywords: survival, adherence to treatment, people living with HIV/ AIDS.Correspondence:Tena Kogoya. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36 A, 57126, Surakarta, Central Java. Email: tena.kogoya76@gmail.com. Phone: +628198869665.Indonesian Journal of Medicine (2017), 3(2): 184-191https://doi.org/10.26911/theijmed.2017.02.03.06